Biochemical, ecological and molecular characterization of Xenorhabdus anantnagensis associated with Steinernema anantnagense from India: evaluating nematode efficacy against Helicoverpa armigera - Krishnapriya Okram; Aashaq Hussain Bhat; Ladoi Drema (نامه انجمن حشره‌شناسی ایران)
This study provides a molecular and phenotypic characterization of an entomopathogenic nematode-bacterium complex isolated from agricultural soil and nematode efficacy against Helicoverpa armigera. The nematode, identified as Steinernema anantnagense KP_CU, was characterized using the internal transcribed spacer (ITS) region of rRNA, revealing 100% similarity with the type population of S. anantnagense. Phylogenetic analysis confirmed its conspecific status within a clade including S. kushidai, S. akhursti, and S. populi. Concurrently, the associated bacterium, identified as Xenorhabdus sp. KP_CU, exhibited 100% similarity in its 16S rRNA sequence with Xenorhabdus anantnagensis XENO-2T, suggesting conspecificity. Phenotypic characterization aligned the bacterium closely with X. anantnagensis, highlighting typical traits such as rod-shaped, gram-negative cells and absence of bioluminescence. Biochemical tests further supported this identification, distinguishing KP_CU from other Xenorhabdus species based on citrate utilization, gelatinase, lysine decarboxylase, urease, arginine dihydrolase, ornithine decarboxylase, glucose oxidation, cytochrome oxidase and indole production. Phylogenetic analysis based on 16S rRNA sequences placed Xenorhabdus sp. KP_CU within a monophyletic clade with X. anantnagensis, along with sister relationships to X. japonica and X. vietnamensis. The bacterial strains also exhibited larvicidal activity against Galleria mellonella and even at the lowest optical density (OD590 = 0.125) induced over 80% larval mortality within merely 24 h post-injection, emphasizing its elevated virulence. The strain KP_CU could kill the wax moth larvae with 38, 16 and 9 IJs at 24, 36 and 48 h, respectively. The nematode isolate KP_CU demonstrated high virulence against H. armigera larvae, with complete mortality achieved within 60 h across all tested inoculum levels. Mortality began at 36 h post-inoculation at 100 IJs/larva and was reached within 24 h at 200 IJs/larva. LD50 values decreased significantly from 38 IJs at 24 h to just 9 IJs at 48 h, indicating potent lethality. Additionally, progeny production showed a dose-dependent increase, though slightly reduced at higher doses, suggesting a trade-off between virulence and reproductive success. These results suggest that S. anantnagense KP_CU could hold potential as a biocontrol agent for H. armigera in agricultural settings in India.